1998
DOI: 10.1084/jem.187.5.787
|View full text |Cite
|
Sign up to set email alerts
|

Selective Expression of a Stable Cell Surface Molecule on Type 2 but Not Type 1 Helper T Cells

Abstract: T helper cell type 1 (Th1) and 2 (Th2) are central to immune regulation. However, no stable cell surface marker capable of distinguishing and separating these two subsets of CD4+ cells has yet been found. Using differential display PCR, we have identified a gene encoding a cell membrane bound molecule, originally designated ST2L, T1, DER4, or Fit, expressed constitutively and stably on the surface of murine Th2s, but not Th1s even after stimulation with a range of immunological stimuli. Antibody against a pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
420
2
7

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 482 publications
(445 citation statements)
references
References 36 publications
16
420
2
7
Order By: Relevance
“…Importantly, we found that naive CD4 1 T cells did not respond to IL-33 in the absence of DCs. This observation is consistent with the fact that naive T cells do not express ST2 and that IL-33 did not induce Th2 cytokines in non-polarized CD4 1 T cells [10,35,36]. The cytokine expression pattern of T cells polarized by IL-33-activated DCs differs from classical Th2 cells by the absence of IL-4 production.…”
supporting
confidence: 87%
“…Importantly, we found that naive CD4 1 T cells did not respond to IL-33 in the absence of DCs. This observation is consistent with the fact that naive T cells do not express ST2 and that IL-33 did not induce Th2 cytokines in non-polarized CD4 1 T cells [10,35,36]. The cytokine expression pattern of T cells polarized by IL-33-activated DCs differs from classical Th2 cells by the absence of IL-4 production.…”
supporting
confidence: 87%
“…1 shows that IL-33 induced no reproducible effect on lymphocyte populations cultured overnight with medium alone (Fig. 1A), reflecting low levels of spontaneous expression of ST2 on the surface of resting T cells ( [2] and data not shown). In contrast, when CD4 + T cells from PBMC were activated overnight with platebound anti-CD3 antibody, phytohemagglutinin (PHA) or staphylococcal enterotoxin B (SEB), the cells polarized to IL-33 in a dose-dependent manner (Fig.…”
Section: Il-33 Induces Polarization and Migration Of Peripheral Bloodmentioning
confidence: 89%
“…Since we have previously shown that ST2 is preferentially expressed on activated Th2 cells [2], we next explored the hypothesis that IL-33 preferentially induced locomotion in Th2 cells. CD4 + T cells purified from PBMC were cultured under Th2 and Th1 differentiation conditions.…”
Section: Il-33 Induces Migration Of Th2 But Not Th1 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of the three forms has been detected in various human tissues and cells, including hematopoietic and endothelial cells [25]. ST2L has been proposed as a marker for Th2 CD4+ T cells since it is selectively expressed on Th2 but not on Th1 CD4+ T cells [26,27] and might be involved in the effector phase of Th2 immune responses [28]. Expression of sST2 protein can be induced in vitro by pro-inflammatory stimuli, like lipo-polysaccaride (LPS), IL-1β, TNF-α and IL-6 in human and murine inflammatory models [25,29].…”
Section: Introductionmentioning
confidence: 99%